Challenging acts of international organizations before national courts - Reinisch, August (OUP OxfordGB, 2010)
Intends to portray the variety of possible forms of challenges against acts of international organizations in national courts and to provide evidence in relation to the following : judicial review of acts of international organisations; challenges are possible before national courts regardless of whether the forum jurisdiction follows a monist or dualist tradition of incorporating international law in to the domestic legal order; human rights review of acts of these organisations by national courts based on internationally accepted principles is more than adequate than a review based on checking their conformity with purely national legal concepts.\n